Formulation and Evaluation of Spherical Crystal of Etoricoxib - Dash, Ranjit (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTThe purpose of this study was to prepare spherical crystal of poorly water soluble drug of Etoricoxib and to know the effect of different polymers on the solubility and dissolution rate of Etoricoxib by using acetone, water, and chloroform as bridging liquid. The Quassi emulsion solvent diffusion technique was mainly used for the method of agglomeration. The polymers like ethyl cellulose, polyvinyl pyrrolidone (PVP K30) were used in spherical agglomeration process. The pure drug and its agglomerates are characterized by Fourier Transform infra red spectroscopy (FTIR).The FTIR studies indicated that there is no chemical changes in the agglomerates of Etoricoxib.The spherical agglomerates with different polymers exhibited increasing in the saturation solubility and dissolution rate. The spherical agglomerates have lower micromeric properties as compared to pure drug. The spherical agglomerates exhibited excellent dissolution rate (82.58 % in 75 minutes) as compared to Etoricoxib. The agglomerates also exhibited higher micrometric properties which indicate good compressibility and packability characteristics.